Which are the most sensitive parameters for suspended solids modelling in free water surface constructed wetlands?. (April 2018) - Gargallo, Sara; Solimeno, Alessandro; Martín, Miguel
Abstract: A large number of input factors are involved in mechanistic models for constructed wetlands simulation. Proper calibration procedure requires identifying which are the most influential ones in the simulation of main interest outputs. Total suspended solids concentration is an essential component in the simulation of eutrophic water treatment. In this paper, a global sensitivity analysis using the Morris method and scaled elementary effects was performed in order to identify which are the most influential input factors in total suspended solids simulation in free water surface constructed wetlands treating eutrophic water. Results indicated that the most influential one was the sedimentation velocity of total suspended solids, followed by parameters related to the resuspension process caused by wind, which presented non-linear or interaction effects. Highlights: A global sensitivity analysis for total suspended solids modelling was conducted. The Morris method and scaled elementary effects methodology were implemented. Sedimentation velocity was pointed out to be the most influential input factor.